Tree diversity and carbon stored in communally managed tropical forests in Yucatan, Mexico - Hurtado-Torres, María Camila; Dupuy-Rada, Juan Manuel; Montañez-Escalante, Patricia; Jiménez-Osornio, Juan (Instituto de Ecología, A.C., 2022)
Sustainable community forest management supports the economy of many rural communities without compromising the capacity of the forest to regenerate and, thus, to provide ecosystem services such as carbon storage. This activity has been widely documented in the Yucatan Peninsula but has been scarcely evaluated in the State of Yucatan. For this research we compared the tree composition, structure, diversity, and carbon stored in aboveground biomass in three areas of a tropical dry forest with different ages of regrowth after forest management in the ejido San Agustín (AAF1, AAF10 and AAF+50 years). In each one, two 1-ha clusters were established consisting of four circular 400 m2 plots, where all trees ≥ 7.5 cm in diameter were identified and measured (diameter and height). We analyzed tree size distribution, species diversity, relative importance value, and aboveground biomass (using allometric equations). The most dominant species was Bursera simaruba and the AAF+50 showed the lowest dominance. The tree diameter distribution did not vary among the forest management areas and showed an inverted J pattern suggesting a high regeneration potential. Diversity did not differ among the management areas, whereas the carbon stored in aboveground biomass did and, was higher in the AAF+50 (65.2 t /ha). The results indicate that the management plan established by the ejido has not affected tree diversity or the regeneration potential and allows a high carbon storage.